Analisis keterampilan berpikir kritis dalam pembelajaran biologi materi sistem reproduksi manusia pada siswa SMA Putra Bangsa Kabupaten Tangerang - Ekasari, Yolinda Cantika; Ani Nikmah; Fitri Rizkiyah; Rizqi Nur Rachmawati; Mona Anju Sansena (Jurnal Kajian Pendidikan IPA, 2024)
This study aims to analyze students’ critical thinking skills in biology learning on the topic of the human reproductive system at SMA Putra Bangsa, Tangerang Regency. A descriptive quantitative method was employed, with data collected using a validated and reliable Likert-scale questionnaire (Cronbach’s Alpha = 0.936). The sample consisted of 43 students from class XI MIPA. The results showed that students’ critical thinking skills were in the moderate category, with 13.3% scoring between 50%–60%. Hypothesis testing revealed no significant relationship between critical thinking skills and learning outcomes (p = 0.609 > 0.05). These findings suggest that enhancing critical thinking skills requires the application of active learning models such as Problem-Based Learning (PBL) or SIMAS ERIC, along with interactive learning media and teacher training